2020
DOI: 10.7326/m20-3742
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Mortality Among Patients Diagnosed With COVID-19: Results From an Integrated Health Care Organization

Abstract: Emerging reports suggest that obese patients who are hospitalized with COVID-19 may have worse outcomes; whether this association extends to those who are not hospitalized is unclear. This study examines the association between obesity and death 21 days after diagnosis of COVID-19 among patients who receive care in an integrated health care system, accounting for obesity-related comorbidities and sociodemographic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

67
464
12
24

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 509 publications
(567 citation statements)
references
References 43 publications
67
464
12
24
Order By: Relevance
“…[4,5] Other large observational studies from the US and the UK using multiple categories of BMI, only found an association between morbid obesity (BMIs above 35 kg/m 2 or 40 kg/m 2 ) and COVID-19 mortality. [37][38][39][40] Our results for high BMIs are consistent with the latter studies, as our analyses revealed BMI was associated in a J-shaped fashion with the risk of COVID-19 related death: only BMIs above 37kg/m 2 and 40kg/m 2 were linked with a higher risk of death after a COVID-19 hospitalisation and after a COVID-19 outpatient diagnosis, respectively. Our findings were also aligned with those of a study conducted in a New York hospital which reported a J-shaped association between BMI and the risk of intubation or death.…”
Section: Possible Explanationssupporting
confidence: 89%
See 2 more Smart Citations
“…[4,5] Other large observational studies from the US and the UK using multiple categories of BMI, only found an association between morbid obesity (BMIs above 35 kg/m 2 or 40 kg/m 2 ) and COVID-19 mortality. [37][38][39][40] Our results for high BMIs are consistent with the latter studies, as our analyses revealed BMI was associated in a J-shaped fashion with the risk of COVID-19 related death: only BMIs above 37kg/m 2 and 40kg/m 2 were linked with a higher risk of death after a COVID-19 hospitalisation and after a COVID-19 outpatient diagnosis, respectively. Our findings were also aligned with those of a study conducted in a New York hospital which reported a J-shaped association between BMI and the risk of intubation or death.…”
Section: Possible Explanationssupporting
confidence: 89%
“…[7] Furthermore, our results provide important insights on the higher risk of COVID-19 related death for low BMIs (≤19kg/m 2 ); while other studies also found this trend in their effect estimates, these were not significant, likely due to their smaller sample sizes. [7,39,40] We also found that mortality risk related to an increased BMI was higher among individuals aged 69 years or younger compared to older adults. Four previous studies are much in line with our findings, while the opposite was reported in a meta-analysis.…”
Section: Possible Explanationsmentioning
confidence: 73%
See 1 more Smart Citation
“…24 Our finding that obesity is associated with increased COVID-19 compatible symptoms among SARS-CoV-2 seropositive individuals provides benchmark data for understanding symptom heterogeneity in mild infections by BMI. We demonstrate that not only are well established measures of severe disease such as hospitalization, intensive care requirements and death more common among obese individuals 5,25,26 , but that obesity is also an important driver of increased symptomatology in non-severe infections. While our data does not provide insights into the mechanism driving these findings, it informs our understanding of symptomatology and obesity, guides our interpretation of epidemiological data, and highlights the potential implication of using passively collected symptom-driven surveillance data to characterize the epidemiology of infectious pathogens.…”
Section: Discussionmentioning
confidence: 80%
“…Even after adjusting for age and obesity-related comorbidities such as diabetes, hypertension and coronary heart disease, obesity remains a strong independent predictor of excess morbidity and mortality. 1,4,5 These findings although concerning are not entirely unexpected. 6 Obesity and poor clinical outcomes have been described with other viral pathogens, most notably influenza A (H1N1) during the 2009 pandemic, when obesity was associated with increased hospitalizations, need for intensive care support, and deaths.…”
Section: Introductionmentioning
confidence: 71%